1997
DOI: 10.1007/s001150050155
|View full text |Cite
|
Sign up to set email alerts
|

Juxtafacettenzysten als raumfordernde intraspinale Prozesse

Abstract: Ganglionic and synovial cysts (juxta-facet cysts) causing nerve root compression are very rare. Magnetic resonance imaging is the best means of diagnosis. The treatment of choice is surgical removal of the cysts, though spontaneous remissions do occur. CT-guided aspiration of the cysts and corticosteroid injection can lead the symptoms to disappear, but only for a short time. In a retrospective study covering a period of 16.5 years, we discovered 24 juxta-facet cysts (10 ganglionic and 14 synovial cysts) with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1999
1999
2006
2006

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Many authors have described these lesions and recognized their propensity to cause nerve root and cauda equina compression. 1,3,4,7,10,11,13,19,25,28,30,32,33,[37][38][39][40][41][42][43]46 Initially thought to be uncommon, 3,4,9,11,19,32,37,38,43,46 synovial cysts have been more recently reported as increasingly recognized causative agents of lumbosacral radicular and/or claudicatory pain. 37,39,41 Refinements in neurodiagnostic imaging and the advent of MR imaging have markedly enhanced the preoperative identification of these lesions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many authors have described these lesions and recognized their propensity to cause nerve root and cauda equina compression. 1,3,4,7,10,11,13,19,25,28,30,32,33,[37][38][39][40][41][42][43]46 Initially thought to be uncommon, 3,4,9,11,19,32,37,38,43,46 synovial cysts have been more recently reported as increasingly recognized causative agents of lumbosacral radicular and/or claudicatory pain. 37,39,41 Refinements in neurodiagnostic imaging and the advent of MR imaging have markedly enhanced the preoperative identification of these lesions.…”
Section: Discussionmentioning
confidence: 99%
“…The advent of MR imaging has markedly improved diagnostic capability and is currently the imaging modality of choice. 3,15,38 Much debate remains regarding the cause of synovial cysts. Traumatic injury 17,19,25,27,29,40,44,45 and segmental instability 5,12,37,41,43,46,47 are the most often cited potential causative factors for the development of synovial cysts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature indicates a minor female preponderance of 53 % with an age range of 16±81 years (mean age 57 years) [1,2,5,6,7,8,9,10,11,12,13,14,15,16,17]. A review of 26 published cases showed a female predominance of 66 % [17].…”
Section: Age and Gendermentioning
confidence: 94%
“…In the third case the bilaterally located cyst was identified 1 year later at the same level. In a total of 137 cases culled from the literature, 68 % arose at L4/5, 15 % at L5/S1, 12 % at L3/4 and 5 % at more proximal levels [2,5,6,8,10,11,12,14,15,22,25]. Few reports specifically mention the side of the cyst.…”
Section: Level and Sidementioning
confidence: 96%